Relationship between eggbeater kick and support scull skills, and isokinetic peak torque - Homma, M. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: Eggbeater kick and support scull are essential basic propulsive techniques in synchronized swimming. The aim of the present study is to ascertain the relationship between muscle strength, and eggbeater kick (EB) skills and vertical position (VP) support skills in elite synchronized swimmers. METHODS: Ten female silver-medalists at the World Championships participated. EB and VP support skills were assessed based on their respective test scores. EB skills were assessed by EB and height (Ht) scores, and VP support skills were assessed by VP and design scores. The isokinetic peak torque for knee flexion and extension (60 or 180°/s), trunk flexion and extension (60 or 120°/s) and shoulder internal and external rotations (60 or 120°/s) were measured using the BIODEX System 3.RESULTS: Both EB and Ht scores significantly correlated with 60°/s (EB: r=.735, Ht: r=.717) and 180°/s (EB: r=.711, Ht: r=.749) (left) knee flexion. Ht score significantly correlated with 60°/s trunk flexion (r=.812). Correlations between EB score and 60 or 180°/s (left) knee flexion per BW (r=.673), and between height score and 60°/s trunk flexion per BW (r=.778) were significant. VP scores significantly correlated with 60°/s (r=.633) and 120°/s (r=.646) right external shoulder rotations per BW. Design scores significantly correlated with 60°/s (R: r=.663) and 120°/s (R: r=.642, L: r=.654) external shoulder rotations per BW. DISCUSSION: From the results, the importance of strengthening the muscles associated with hip flexion such as the hamstrings, rectus abdominis, and psoas major was suggested. These findings are related to the EB techniques for improving skills, which are executed with the knees and heels at higher positions. The significant relationship between external shoulder rotation and VP support skills might have been due to the specificity of support scull movements. The support scull is a rotational movement of the forearms with bent elbows, and it is an unusual movement where a swimmer bends the elbows and externally rotates the shoulder while supinating the forearms. Therefore, rather than individual differences in internal rotation, those in external rotation are closely related to the support scull skills. To improve the support scull skills, upper arm abductors such as the infraspinatus and teres minor should be trained and the muscles around the scapula should be strengthened in proper balance.